GART promotes the proliferation and migration of human non-small cell lung cancer cell lines A549 and H1299 by targeting PAICS-Akt-β-catenin pathway - Chen, Zhuo; Ding, Yu-Heng; Zhao, Mei-qi; Zhang, Yong-jun; Sun, Meng-Ying; Zhang, Ai-Qin; Qian, Xiang; Ji, Xu-Ming (Frontiers in Oncology, 2025)
BackgroundLung adenocarcinoma (LUAD) is the primary subtype of Non-small cell lung cancer (NSCLC) and a serious threat to human health. However, the precise molecular mechanisms in lung cancer remain largely unexplored.MethodsHerein, we performed proteomic analysis in a cohort of 20 LC primary tumors and their paired normal tissues. The expression levels and prognostic value of hub proteins were also explored in LUAD using public databases. Glycinamide ribonucleotide transformylase (GART) expression was detected by qRT-PCR in LC cell lines. The roles of GART were assessed by CCK-8, colony formation, Wound healing assays, and xenograft tumor model. Expression levels of the PAICS-Akt-β-catenin pathway were estimated through qRT-PCR and western blot assays.ResultsThe proteomic analysis of tumor tissues of LC indicated that 263 proteins were upregulated and 194 were downregulated. Bioinformatics analysis showed that differentially expressed proteins were mainly associated with the regulation of apoptotic process and cell adhesion, PI3K-Akt signaling pathway, Purine metabolism, and Wnt signaling pathway. The expression of hub proteins EPRS, GART, HSPE1, and RPS6 was much higher in LUAD tissues than in normal tissues analyzed by the Ualcan database. Overexpression of GART represented a poor prognosis in LUAD patients. Additionally, the knockdown of GART effectively inhibited the cell proliferation and migration of LC cells both in vitro and in vivo. Mechanistically, qRT-PCR and western blot analyses suggested that GART deletion could inhibit the activation of the PAICS-Akt-β-catenin pathway in vivo.ConclusionsOur study indicated a tumor-promoting function of GART in LC through the regulation of the PAICS-Akt-β-catenin axis, and it may be used as a therapeutic target for NSCLC.